Impact of altitude on Covid-19 mortality in Colombia: a cross-sectional study - Diaz-Brochero, Candida R. (2023)
Objective. To estimate the proportion of deaths in confirmed cases according to altitude categories (low, medium, and high), and to evaluate a possible association between altitude and COVID-19 mortality in Colombia during the first two waves of the pandemic. Methods. Cross-sectional, analytical study. Adults residing in Colombia during 2020, with microbiological confirmation of SARS-CoV-2 infection were included. We calculated CFR using a binomial confidence interval, dividing altitude in three categories. We also performed a logistic regression model to evaluate the association between altitude and COVID-19 mortality. Results. Data on confirmed cases of COVID-19 during the period from March 06, 2020, to December 15, 2020, reported in 1,112 municipalities in Colombia were analyzed. A total of 994,738 confirmed cases were reported, including 32,034 deaths (0,03%). The mean age of cases was 39,8 years and 504,476 (50,4%) were male. The altitude range varied between 0 m to 3,350 m. The CFR was 0,042 (CI 95% 0,042 - 0,043; p value <0.001); 0,027 (CI 95% 0,027 - 0,028; p value <0.001) and 0,026 (CI 95% 0,025 - 0.026; p value <0.001) for low, middle, and high altitude, respectively. We found that for each km increase in altitude, the probability of dying from COVID-19 decreases by 20% (OR 0.8; 95% CI 0.785 - 0.815; p value <0.001), controlled by biological sex, age and number of inhabitants per municipality. Conclusions. Our results demonstrate that the altitude is a potential protective factor against COVID-19 mortality according to data from a Colombian population during the first two waves of the epidemic.